1992
DOI: 10.1136/jnnp.55.6.431
|View full text |Cite
|
Sign up to set email alerts
|

Measuring visual neglect in acute stroke and predicting its recovery: the visual neglect recovery index.

Abstract: An overall measure of the recovery of visual neglect in patients with an acute stroke is described: The "Visual Neglect Recovery Index" (VNRI) expresses the amount of visual neglect on a battery of visual neglect tests as a percentage of complete recovery from the maximal visual neglect measurable. The principles underlying the development of the index are similar to those involved in the development of the Motricity Index for hemiplegia. A population of 68 survivors of stroke who presented with visual neglect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
122
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(137 citation statements)
references
References 19 publications
10
122
0
4
Order By: Relevance
“…The cut-off score for line bisection was determined by scoring guidelines provided for the Behavioral Inattention Test (Wilson et al, 1987). Using this definition neglect was present in nearly 50% of the right hemisphere stroke patients studied previously by Buxbaum et al (2004), which was consistent with previous reports of neglect prevalence (Stone et al, 1992).…”
Section: Determination Of Neglectsupporting
confidence: 91%
“…The cut-off score for line bisection was determined by scoring guidelines provided for the Behavioral Inattention Test (Wilson et al, 1987). Using this definition neglect was present in nearly 50% of the right hemisphere stroke patients studied previously by Buxbaum et al (2004), which was consistent with previous reports of neglect prevalence (Stone et al, 1992).…”
Section: Determination Of Neglectsupporting
confidence: 91%
“…Not all investigators have found high perseveration rates following left hemisphere damage [6]. Second, we did not calculate an index of neglect severity as in some recent studies [37,38]. Although we feel the absolute number of neglect responses is an appropriate measure and the data is clear (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…Neglect is a common consequence of right-hemisphere stroke. Its reported incidence ranges from 13% (Stone, Patel, Greenwood, & Halligan, 1992) to 81% of patients with right-hemisphere stroke (Sunderland, Wade, & Langton Hewer, 1987), presumably reflecting differences in subject inclusion criteria, lesion location, and assessment procedures (see Bowen, McKenna, & Tallis, 1999); a number of recent studies indicate that about 50% of patients exhibit the disorder (Buxbaum, Ferraro, Veramonti, et al, 2004;Mapstone et al, 2003). Neglect may also be observed in patients with left-hemisphere stroke, but it is more common and more severe in association with right-hemisphere lesions (Ringman, Saver, Woolson, Clarke, & Adams, 2004;Gainotti, 1972).…”
Section: Neglect and Related Disorders: Scope Of The Problemmentioning
confidence: 99%